Dimensions of Performance Measurement in Digital Content Marketing - Koskinen, Juuso (2024)
Companies strive to facilitate a customer-centric approach in their marketing efforts in a tight, competitive environment. As a result, digital content marketing (DCM) has become an essential marketing attribute in organizations with its inbound logic of attracting customers. However, marketers face significant challenges in providing convincing results of the DCM marketing performance measurement (MPM), a topic studied only little by academics. Therefore, this research aims to produce valuable information about DCM performance goals, internal DCM performance factors, DCM performance measurement practices, and their mutual relationship. The study’s data was collected via qualitative interviews targeting marketing managers. The data obtained was analyzed using thematic analysis with an abductive approach.